Hegemoni Ketua Partai Terhadap Presiden dalam Majalah Tempo Edisi 13-19 April 2015 (Studi Analisis Wacana Kritis) - Hasan, Moh Khalid; Wafi, Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to describe Jokowi Mega's hegemony based on the discourse dimension (mesostructural) based on the socio-cultural dimension (macrostructural) in the April 13-19, 2015 edition of Tempo magazine. This type of research is qualitative research. This research uses a critical discourse analysis (AWK) approach, according to Darma, the AWK discussion focuses on the nature of ideological contextualization. The approach to ideology must pay attention to its effect on the form and meaning as well as the structure of the discourse which will later play a role in shaping and shaping ideology. The results of the analysis showed that the April 13-19, 2015, edition of Tempo magazine contained a statement from the party chairman, who wanted the presidential administration to follow the party constitution. The three dimensions are the textual (microstructural) dimension in the magazine studied, using a lot of diction and conjunctions. The discourse dimension (mesostructural) is a journalist's review of the hegemony carried out by Megawati against the President and proves that Tempo Magazine is not affiliated with the government. The practical socio-cultural (macrostructural) dimension, which focuses on political issues contained in Tempo magazine.